THE IMPORTANCE OF APPROPRIATE ACCOMMODATIONS IN SUPPORTING THE PSYCHOLOGICAL WELL-BEING OF STUDENTS WITH SPECIAL NEEDS AT PGRI ADI BUANA UNIVERSITY IN SURABAYA - Amelia Rizky Idhartono; Ana Rafikayati; Nurul Hidayati; Reza Rachmadtullah; Alya Adjeng Kartikasari; Novriyana Santri Yasin; Alsyah Asfarina Subekti (Jurnal Konseling Pendidikan Islam, 2026)
Inclusive higher education is a crucial pillar in promoting social justice in the field of education, particularly for students with special needs who are entitled to equal access to educational services. Universitas PGRI Adi Buana Surabaya (UAB) is one of the higher education institutions implementing inclusive education by providing reasonable accommodations, including adjustments to facilities, learning methods, as well as social and psychological support. Reasonable accommodations are essential not only to facilitate academic participation but also to support the psychological well-being of students with special needs. This study aims to describe the forms and implementation of reasonable accommodations for students with special needs and to analyze their urgency in supporting students’ psychological well-being at UAB. The research employs a qualitative approach using a case study method. The research subjects include students with special needs, lecturers, administrative staff, and non-disabled students who have directly interacted with students with special needs. Data were collected through in-depth interviews, observations, and documentation, and analyzed descriptively to examine the relationship between the availability of reasonable accommodations and students’ psychological well-being. The findings are expected to demonstrate that reasonable accommodations play a significant role in enhancing various aspects of the psychological well-being of students with special needs. These findings are expected to serve as a foundation for policy development and strategic planning in higher education institutions, particularly UAB, to strengthen inclusive education systems and foster a campus environment that is welcoming and accessible to all students.